Unknown multiple object tracking using 2D lidar and video camera - Kwak, K.; Kim, J. -S.; Min, J.; Park, Y. -W. (INST ENGINEERING TECHNOLOGY-IET, 2014)
A multisensor fusion-based unknown object detection and tracking approach is presented. The approach consists of two new algorithms: (i) object segmentation by boundary detection and (ii) data association by integer programming. The proposed approach tightly combines the information from a single-line scanning lidar and a camera. The performance of the proposed algorithm is evaluated by comparing with a state-of-the-art method and is demonstrated with real datasets obtained from a moving platform.